Directions of Deep Brain Stimulation for Epilepsy and Parkinson’s Disease - Ying-Chang Wu; Ying-Siou Liao; Wen-Hsiu Yeh; Sheng-Fu Liang; Sheng-Fu Liang; Fu-Zen Shaw; Fu-Zen Shaw (Frontiers in Neuroscience, 2021)
BackgroundDeep brain stimulation (DBS) is an effective treatment for movement disorders and neurological/psychiatric disorders. DBS has been approved for the control of Parkinson disease (PD) and epilepsy.ObjectivesA systematic review and possible future direction of DBS system studies is performed in the open loop and closed-loop configuration on PD and epilepsy.MethodsWe searched Google Scholar database for DBS system and development. DBS search results were categorized into clinical device and research system from the open-loop and closed-loop perspectives.ResultsWe performed literature review for DBS on PD and epilepsy in terms of system development by the open loop and closed-loop configuration. This study described development and trends for DBS in terms of electrode, recording, stimulation, and signal processing. The closed-loop DBS system raised a more attention in recent researches.ConclusionWe overviewed development and progress of DBS. Our results suggest that the closed-loop DBS is important for PD and epilepsy.